Continuous vs. discontinuous purification of isolated human islets: functional and morphological comparison - Buemi, Antoine; Mouard, Nizar I.; Darius, Tom; Devresse, Arnaud; Kanaan, Nada; Gianello, Pierre; Mourad, Michel (Frontiers in Endocrinology, 2023)
Background The COBE 2991 cell processor, commonly used for pancreatic islet isolation, is no longer distributed in Europe, leading to a search for alternative purification procedures with equivalent efficacy. The aim of this study was to evaluate the efficacy of an alternative method based on the discontinuous purification of islets. Methods The conventional isolation procedure using a standard continuous islet purification with COBE 2991 of n = 4 human pancreas was compared to n = 8 procedures using a discontinuous purification with a “bottle” method from donors of similar characteristics. Islet equivalents, purity, and dynamic glucose-stimulated insulin secretion were evaluated. Results A similar islet yield was obtained using continuous vs. discontinuous purification methods (76,292.5 ± 40,550.44 vs. 79,625 ± 41,484.46 islet equivalents, p = 0.89). Islets from both groups had similar purity (78.75% ± 19.73% vs. 55% ± 18.16%, p = 0.08) and functionality both in terms of stimulation index (3.31 ± 0.83 vs. 5.58 ± 3.38, p = 0.22) and insulin secretion (1.26 ± 0.83 vs. 1.53 ± 1.40 mean AUC, p = 0.73). Moreover, the size of the islets was significantly larger in the discontinuous vs. continuous purification group (19.2% ± 10.3% vs. 45.4% ± 18.8% of islets less than 100 µm, p = 0.0097 and 23.7% ± 5.3% vs. 15.6% ± 5.8% of 200–250 µm islet size, p = 0.03). Conclusion Compared to the conventional purification procedure, discontinuous purification with a bottle method shows similar results with regard to isolation yield and islet secretory function. Furthermore, this alternative technique allows for obtaining larger islets.